2000
DOI: 10.1038/76694
|View full text |Cite
|
Sign up to set email alerts
|

An ‘automatic pilot’ for the hand in human posterior parietal cortex: toward reinterpreting optic ataxia

Abstract: We designed a protocol distinguishing between automatic and intentional motor reactions to changes in target location triggered at movement onset. In response to target jumps, but not to a similar change cued by a color switch, normal subjects often could not avoid automatically correcting fast aiming movements. This suggests that an 'automatic pilot' relying on spatial vision drives fast corrective arm movements that can escape intentional control. In a patient with a bilateral posterior parietal cortex (PPC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

41
406
6
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 639 publications
(469 citation statements)
references
References 38 publications
41
406
6
7
Order By: Relevance
“…Strikingly, when a single transcranial magnetic stimulation pulse was applied, at hand movement onset, over the PPC, these path corrections were disrupted, and the subject pointed to the first target location. This result was recently replicated in a clinical study involving a patient presenting with bilateral ischemic lesions of the PPC (Pisella et al, 2000). Although this patient was able to accurately point to stationary targets, she presented a dramatic inability to correct her ongoing movements when the target location was slightly modified at movement onset.…”
Section: Functional Anatomy Of Movement Guidancesupporting
confidence: 53%
“…Strikingly, when a single transcranial magnetic stimulation pulse was applied, at hand movement onset, over the PPC, these path corrections were disrupted, and the subject pointed to the first target location. This result was recently replicated in a clinical study involving a patient presenting with bilateral ischemic lesions of the PPC (Pisella et al, 2000). Although this patient was able to accurately point to stationary targets, she presented a dramatic inability to correct her ongoing movements when the target location was slightly modified at movement onset.…”
Section: Functional Anatomy Of Movement Guidancesupporting
confidence: 53%
“…Previous functional imaging studies (Imamizu et al 2003(Imamizu et al , 2004 also supported the MOSAIC model and suggested that a prefrontal region (Brodmann area 46) contributes to the predictor while loops between the parietal regions (Pisella et al 2000) and the cerebellum contribute to the estimator. The current behavioral study in the context of previous computational (Wolpert et al 1995;Wolpert and Kawato 1998;Kawato 1999) and imaging studies (Imamizu et al 2004) suggests that, to achieve adaptation to multiple environments, a predictive mechanism, possibly located in the frontal cortex, needs to switch multiple internal models residing in the cerebellum.…”
Section: Discussionmentioning
confidence: 67%
“…Desmurget and colleagues have provided a tool to determine behaviorally whether the dorsal stream is critically involved in specific aspects of a task (Desmurget et al, 1999;Pisella et al, 2000). Using transcranial magnetic stimulation and a patient study, they showed that part of the dorsal route (the posterior parietal cortex) is necessary for fast (less than 150-ms latency) corrections of ongoing pointing movements to perturbations of object locations.…”
mentioning
confidence: 99%